Shisa3 brakes resistance to EGFR-TKIs in lung adenocarcinoma by suppressing cancer stem cell properties - Jiahui Si (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Although EGFR tyrosine kinase inhibitors (EGFR-TKIs) are beneficial to lung adenocarcinoma patients with sensitive EGFR mutations, resistance to these inhibitors induces a cancer stem cell (CSC) phenotype. Here, we clarify the function and molecular mechanism of shisa3 as a suppressor that can reverse EGFR-TKI resistance and inhibit CSC properties. Methods The suppresser genes involved in EGFR-TKI resistance were identified and validated by transcriptome sequencing, quantitative real-time PCR (qRT-PCR) and immunohistochemistry. Biological function analyses, cell half maximal inhibitory concentration (IC50), self-renewal, and migration and invasion capacities, were detected by CCK8, sphere formation and Transwell assays. Tumorigenesis and therapeutic effects were investigated in nonobese diabetic/severe combined immunodeficiency (nod-scid) mice. The underlying mechanisms were explored by Western blot and immunoprecipitation analyses. Results We found that low expression of shisa3 was related to EGFR-TKI resistance in lung adenocarcinoma patients. Ectopic overexpression of shisa3 inhibited CSC properties and the cell cycle in the lung adenocarcinoma cells resistant to gefitinib/osimertinib. In contrast, suppression of shisa3 promoted CSC phenotypes and the cell cycle in the cells sensitive to EGFR-TKIs. For TKI-resistant PC9/ER tumors in nod-scid mice, overexpressed shisa3 had a significant inhibitory effect. In addition, we verified that shisa3 inhibited EGFR-TKI resistance by interacting with FGFR1/3 to regulate AKT/mTOR signaling. Furthermore, combinational administration of inhibitors of FGFR/AKT/mTOR and cell cycle signaling could overcome EGFR-TKI resistance associated with shisa3-mediated CSC capacities in vivo. Conclusion Taken together, shisa3 was identified as a brake to EGFR-TKI resistance and CSC characteristics, probably through the FGFR/AKT/mTOR and cell cycle pathways, indicating that shisa3 and concomitant inhibition of its regulated signaling may be a promising therapeutic strategy for reversing EGFR-TKI resistance.